2021
DOI: 10.3390/en14175377
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sizing of Hybrid Wind-Solar Power Systems to Suppress Output Fluctuation

Abstract: Harnessing wind energy is one of the fastest-growing areas in the energy industry. However, wind power still faces challenges, such as output intermittency due to its nature and output reduction as a result of the wake effect. Moreover, the current practice uses the available renewable energy resources as a fuel-saver simply to reduce fossil-fuel consumption. This is related mainly to the inherently variable and non-dispatchable nature of renewable energy resources, which poses a threat to power system reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In the second stage, solar PV and batteries are added to the existing wind farm to reduce the power fluctuations on the output of the HRPP generation. Similarly, Al-Shereiqi et al [32] created a strategy that determines the optimal size of hybrid wind-solar photovoltaic power systems that use heuristic optimization with a numerical iterative algorithm such that the output fluctuation is minimized. A sizing exercise was performed to reduce the impact of renewable intermittency and to generate the maximum output power to the grid at a constant level based on the availability of renewable energy resources.…”
Section: Overview Of Hybrid Renewable Power Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second stage, solar PV and batteries are added to the existing wind farm to reduce the power fluctuations on the output of the HRPP generation. Similarly, Al-Shereiqi et al [32] created a strategy that determines the optimal size of hybrid wind-solar photovoltaic power systems that use heuristic optimization with a numerical iterative algorithm such that the output fluctuation is minimized. A sizing exercise was performed to reduce the impact of renewable intermittency and to generate the maximum output power to the grid at a constant level based on the availability of renewable energy resources.…”
Section: Overview Of Hybrid Renewable Power Plantsmentioning
confidence: 99%
“…The studies in [26][27][28] concluded that adding a battery storage system would increase costs, but did not provide a comparative basis for other solutions that might still be beneficial (e.g., overplanting with the same technology or adding other renewable source technologies). Furthermore, the optimized configuration of an HRPP is mainly performed on a single case study [29][30][31][32][33], which may undermine the potential for generalizing the results to other locations. The technical and economic performance of an HRPP in utilityscale applications that participates in the DA market depends on the complementarity profile of the renewable energy resources feeding the technologies that constitute the HRPP [35].…”
Section: Overview Of Hybrid Renewable Power Plantsmentioning
confidence: 99%
“…For example, in [16], the utilization of the ESS of a virtual power plant was investigated to optimize trading in the electricity market. Frequently, studies investigating the sizing of an ESS for a PV-wind power system have included the economical aspect in the sizing algorithm-for example in [17][18][19]. However, as the main purpose of an ESS is to mitigate the fast power fluctuations of a PV-wind power plant, the temporal resolution of the measured or modelled generated power of the power plant should be very high.…”
Section: Introductionmentioning
confidence: 99%
“…However, the temporal resolution of data utilized in many of the previous studies is generally significantly lower than 10 Hz. For example, the length of the data time step was 10 min in [14,17,18] and 1 min in [13].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in the present study, solar and wind power generations are combined to create a hybrid power system. This system, consisting of two unpredictable energy sources, will produce fluctuating output energy and thus cannot ensure the minimum level of power continuity required by the load [1][2][3]. Combining the renewable hybrid system with batteries as a storage system, in order to increase the duration of energy autonomy, will make optimal use of the utilized renewable energy resources and this, in turn, can guarantee high supply reliability.…”
Section: Introductionmentioning
confidence: 99%